(untitled) (AYUSHDHARA, 2017)
Diagnosis is a very vital aspect of Ayurvedic treatment. Diagnosis according to Ayurveda is to find out root cause of disease. Unless the proper diagnosis is done, it is difficult to provide medicine & cure the disease. To give permanent relief, the root cause has to be removed. The causative factors can be the food, life style or some external factors like bacteria, viruses, epidemiology etc. In Ayurveda the diagnosis and treatment of disease is always individual to each patient. As Ayurveda treats according to the constitution of an individual (Prakriti), it is known as highly accurate and personalized method of analyzing diseases. All disease are caused by aggravation & imbalance of ‘ Tridosha’ i.e., Vata, Pitta, Kapha. The Tridosha aggravation may occur due to the intake of improper diet, life style & Mandagni which need to be diagnosed properly by Ayurvedic method for best result. In the beginning most of the student & practitioners find that it is very difficult to diagnose a disease on the basis of Ayurvedic principles. It has need of knowledge, examination skill, logical thinking and continuous practice. Modern medical practices will often pacify the symptoms without addressing the cause. But in diagnostic point of view modern tools like CT scan, MRI, Haemogram, ECG, 2D Echo etc. are very useful in critical condition. This article discusses about some diagnostic approaches of Ayurveda as tool for Nidan as well as role of modern diagnostic method over Ayurvedic nidan.